Microglial cells: Sensors for neuronal activity and microbiota-derived molecules - D’Alessandro, Giuseppina; Marrocco, Francesco; Limatola, Cristina (Frontiers in Immunology, 2022)
Microglial cells play pleiotropic homeostatic activities in the brain, during development and in adulthood. Microglia regulate synaptic activity and maturation, and continuously patrol brain parenchyma monitoring for and reacting to eventual alterations or damages. In the last two decades microglia were given a central role as an indicator to monitor the inflammatory state of brain parenchyma. However, the recent introduction of single cell scRNA analyses in several studies on the functional role of microglia, revealed a not-negligible spatio-temporal heterogeneity of microglial cell populations in the brain, both during healthy and in pathological conditions. Furthermore, the recent advances in the knowledge of the mechanisms involved in the modulation of cerebral activity induced by gut microbe-derived molecules open new perspectives for deciphering the role of microglial cells as possible mediators of these interactions. The aim of this review is to summarize the most recent studies correlating gut-derived molecules, as well as dysbiotic events, to alteration of brain functioning, and the contribution of microglial cells.